Effect of multiparity and ethnicity on the risk of development of diabetes: a large population‐based cohort study. Issue 11 (21st August 2017) - Almahmeed, B.; Shah, B. R.; Mukerji, G.; Ling, V.; Booth, G. L.; Feig, D. S.
Abstract: Aims: To investigate the relationship between increasing parity and diabetes in a large, population‐based cohort, and to examine if this relationship is different among high‐risk ethnic groups. Methods: A population‐based, retrospective cohort study was performed in 738 440 women aged 18–50 years, who delivered babies in Ontario between 1 April 2002 and 31 March 2011. Diabetes incidence postpartum was calculated for each parity and ethnic group. A multivariable analysis of the effect of parity and ethnicity on the incidence of diabetes was performed using a Cox proportional hazards model, adjusting for confounders. Results: The diabetes incidence rate per 1000 person‐years was 3.69 in women with 1 delivery, 4.12 in women with 3 deliveries and 7.62 in women with ≥5 deliveries. Women with ≥3 deliveries had a higher risk of developing diabetes compared with women with 1 delivery [adjusted hazard ratios 1.06 (95% CI 1.01–1.11) for 3 deliveries, 1.33 (95% CI 1.25–1.43) for 4 deliveries and 1.53 (95% CI 1.41–1.66) for ≥5 deliveries). A similar rise in risk could be seen in Chinese and South‐Asian women, with the most influence in Chinese women [hazard ratio 4.59 (95% CI 2.36–8.92) for ≥5 deliveries]. Conclusions: There was a positive and graded relationship between increasing parity and risk of development of diabetes. The influence of parity was seen in all ethnicities. This association may be partly related to increasing weight gain and retention with increasing parity, or deterioration in β‐cell function. This merits further exploration. What's new?: The relationship between parity and the development of diabetes remains unclear, especially among high‐risk ethnic groups. Our study showed a positive and graded relationship between increasing parity and the risk of development of diabetes, even after adjustment for gestational diabetes and other confounders. This effect was seen in all ethnicities, but most notably in those of Chinese ethnicity. These findings serve to clarify the association between parity and the development of diabetes in a very large, population‐based study, and highlight the importance of early screening and intervention in these high‐risk groups.